EFEK PENGHAMBATAN TERHADAP PERTUMBUHAN TUMOR PARU DAN UJI KETOKSIKAN AKUT EKSTRAK KAPSUL CHANG SHEUW TIAN RAN LING YAO PADA MENCIT (MUS MUSCULUS) DAN TIKUS (RATUS TANEZUMI) - Fudholi, Ahmad; Meiyanto, Edy; Donatus, Imono Argo; Nurrochmad, Arief; Hakim, Arief Rahman; Murwanti, Retno (JURNAL BIOLOGI INDONESIA, 2008)
Inhibitory Phases Effect of The Lung Cancer And Acute Toxicity of Chang Sheuw Tian RanLing Yao Capsule Extracts in House mice (Mus musculus) and Rat (Ratus tanezumi). Effortsto find anticancer agents have been developed nowadays, some of them are focused in traditionalherbs. One of the available products in the market that claims effective to cure cancer isthe Chang Sheuw Tian Ran Ling Yao, PT. Daun Teratai extract containing CAPSULE (CSTRLYextract). The aim of this study is to examine of confession of some people which are usingthe useful of medicine CSTRLY extract capsule through inhibitor laboratory effect of theCSTRLY extract in the initiation and post initiation phases of the lung cancer in mice and ratsthat had been induced by eather Benzo[?]pyrene (BP) or Dimetilbenz[?]antrazene (DMBA)and to clarify the potency of acute toxicity and specific toxic manifestations of thephytopharmaca.The results showed that the CSTRLY extract can reduce the cancer incidence caused bycarcinogen, BP and DMBA. Moreover, the extract can also inhibit the cancer growth in themice and rats, especially in the early post-initiation phase. Further, the histopathologicalevaluation showed that up to the highest dose level that technically could be administrated tothe animals (12500 mg/kg bw), no animal death was occurred. Furthermore, the ADG values formale and female rats indicated no significant different (P > 0.05) that relative to the controlgroup. No animals were shows physical symptom as a toxic manifestation. It?s indicated thatthe phytopharmaca no influenced to somatomotor and nervous system. Within the dose rangeadministrations, no detectable morphological toxic effects or histophatological changes of theliver, spleen, heart, and lungs were observed. the acute toxicity value of Chang Sheuw TianRan Ling Yao Capsule was very low (or minimal almost non-toxic with LD50 > 12500 mg/kg bw)and the spectrum of toxic effects of the phytopharmaca were considered negligible.Key words: Ekstract, CSTRLY, mice and rat, BP, DMBA, carsinogenesis, lung cancer